Metaphor and boundary (Lebenswelt. Aesthetics and philosophy of experience., 2011)
The use of metaphors play in Kantian thought a fundamental role. In my paper I argue that Reimarus’ Logic could be considered as a source for Kant's use of some metaphors. In his Logic, in fact, Reimarus anticipates the geographical metaphor by which it is possible to distinguish between limits and boundary, to draw the map of reason and to put her in front of a court. The aim of my analysis is to show that Reimarus’ Logic could be considered as a turning point in Wolffian philosophy on the topic of the definition of experience in relation to unity of the system.